1992
DOI: 10.2307/2135718
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abuse as a Factor in Adolescent Pregnancy and Child Maltreatment

Abstract: Two-thirds of a sample of 535 young women from the state of Washington who became pregnant as adolescents had been sexually abused: Fifty-five percent had been molested, 42 percent had been victims of attempted rape and 44 percent had been raped. Compared with adolescent women who became pregnant but had not been abused, sexually victimized teenagers began intercourse a year earlier, were more likely to have used drugs and alcohol and were less likely to practice contraception. The abused adolescents were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
171
2
12

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(193 citation statements)
references
References 15 publications
4
171
2
12
Order By: Relevance
“…Finally, adolescent mothers are also more likely than older mothers from the same backgrounds to have a history of aggressive and delinquent behaviors (Miller-Johnson et al, 1999;Woodward, Fergusson, & Horwood, 2001) and are more likely to have had mental health problems (Deal & Holt, 1998;Horwitz, Klerman, Kuo, & Jekel, 1991) or exposure to childhood maltreatment (Boyer & Fine, 1992;Smith, 1996). Adolescents are still maturing themselves, and some aspects of adolescent brain maturation and cognitive development appear to be independent of pubertal processes and continue long after puberty is over (Dahl, 2004).…”
Section: Introduction: Early Language and Emerging Literacymentioning
confidence: 99%
“…Finally, adolescent mothers are also more likely than older mothers from the same backgrounds to have a history of aggressive and delinquent behaviors (Miller-Johnson et al, 1999;Woodward, Fergusson, & Horwood, 2001) and are more likely to have had mental health problems (Deal & Holt, 1998;Horwitz, Klerman, Kuo, & Jekel, 1991) or exposure to childhood maltreatment (Boyer & Fine, 1992;Smith, 1996). Adolescents are still maturing themselves, and some aspects of adolescent brain maturation and cognitive development appear to be independent of pubertal processes and continue long after puberty is over (Dahl, 2004).…”
Section: Introduction: Early Language and Emerging Literacymentioning
confidence: 99%
“…Although poverty 2 and childhood physical [3][4][5][6][7] and sexual [1][2][3][4][5][6][7][8] abuse have been associated with an increased risk of pregnancy among adolescent girls, risk factors for male involvement in teen pregnancy have not been widely investigated. Elevated rates of academic and conduct problems, substance abuse, 9,10 previous forced sexual contact, 11 and a greater number of sexual partners 12 have been reported among teenage fathers, which may be symptoms of childhood exposure to abuse and domestic violence.…”
mentioning
confidence: 99%
“…Only 28 percent of the victimized teens used birth control at first intercourse compared to 49 percent of their non-victimized peers (Boyer & Fine, 1992). Another U.S. study confirmed that women survivors of childhood sexual abuse are nearly three times more likely than non-victimized youth to become pregnant before the age of 18 (Zierler et al, 1991).…”
Section: Implications For International Developmentmentioning
confidence: 97%
“…Through its impact on future sexual and drug using behavior, sexual abuse in childhood also appears to increase an individual's risk of contracting STDs and HIV in adulthood (Boyer & Fine, 1992;Zierler et al, 1991;Finkelhor, 1987;Cassese, 1993;Paone & Chavkin, 1993). In one study of 407 randomly selected men and women on the island of Barbados, sexual abuse in childhood emerged as the single most important determinant of high risk sexual activity during adolescence for both women and men (Handwerker, 1993).…”
Section: Implications For International Developmentmentioning
confidence: 99%